2022
DOI: 10.1002/advs.202205215
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Inhibition of Maize Seed‐Borne Fusarium Using a Bacillus‐Dominated Rhizospheric Stable Core Microbiota with Unique Cooperative Patterns

Abstract: Seed-borne pathogens can inhabit the rhizosphere and infect the plant after germination. The rhizosphere microbiome plays critical roles in defending against seed-borne pathogens. However, the assembly of a core rhizosphere microbiome to suppress seed-borne pathogens is unknown. Here, the root-associated microbiome is infested with seed-borne Fusarium in sterile environment, while the root-associated microbiome is not infested when it interacts with the native soil microbiome across maize cultivars, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The top‐down strategy refers to the gradual selection of key microbial agents from environmental samples based on physiological and functional screening (Lawson et al, 2019 ). Xun et al ( 2023 ) used two strategies, progressive dilution and rhizodepositional attraction, to identify the core rhizobacteria taxa responsible for the suppression of maize seed‐borne Fusarium . Consequently, a bacterial consortium was constructed using these keystone strains and optimized according to superior community stability and disease suppression capability, resulting in a simplified SynCom composed of eight strains from the genus of Bacillus , Burkholderia , Enterobacter , Lysobacter , Stenotrophomonas , Pseudoxanthomonas , Pseudomonas , and Acinetobacter .…”
Section: Practical and Emerging Strategies For Enhancing The Biocontr...mentioning
confidence: 99%
“…The top‐down strategy refers to the gradual selection of key microbial agents from environmental samples based on physiological and functional screening (Lawson et al, 2019 ). Xun et al ( 2023 ) used two strategies, progressive dilution and rhizodepositional attraction, to identify the core rhizobacteria taxa responsible for the suppression of maize seed‐borne Fusarium . Consequently, a bacterial consortium was constructed using these keystone strains and optimized according to superior community stability and disease suppression capability, resulting in a simplified SynCom composed of eight strains from the genus of Bacillus , Burkholderia , Enterobacter , Lysobacter , Stenotrophomonas , Pseudoxanthomonas , Pseudomonas , and Acinetobacter .…”
Section: Practical and Emerging Strategies For Enhancing The Biocontr...mentioning
confidence: 99%
“…One or several key strains in SynComs are dominant, and the other strains help the plant produce stress resistance to pathogenic bacteria by assisting key bacterial communities. 113 The inoculants may use metabolites to defend those friendly to their functions and attack those who do not support the growth of microorganisms with similar functions to form SynComs to promote plant immunity to diseases. 114 The effect of a single strain in SynComs on plants is not apparent, but the synergistic effect of several strains forming the SynComs has a more significant impact on the resistance of plants to pathogens.…”
Section: ■ Syncoms In Plant Growthmentioning
confidence: 99%
“…There are various ways to promote plant growth in stable SynComs. One or several key strains in SynComs are dominant, and the other strains help the plant produce stress resistance to pathogenic bacteria by assisting key bacterial communities . The inoculants may use metabolites to defend those friendly to their functions and attack those who do not support the growth of microorganisms with similar functions to form SynComs to promote plant immunity to diseases .…”
Section: Syncoms In Plant Growthmentioning
confidence: 99%
“…Currently, attempts have been made to introduce synthetic communities (SynCom) that include multiple microbial strains into sterile or non inhibitory soils [ 91 ]. The key to synthesizing a community is to optimize its ability to inhibit pathogens using core microorganisms, which have an inhibitory effect that exceeds that of single strains and randomly formed microbial communities [ 92 ]. Studies have found that the optimized synthetic community exhibits a unique cooperative pattern, including key strains that have inhibitory effects on pathogenic microorganisms through the synthesis of antagonistic substances, while other members enhance their function by promoting the growth of key strains and plant growth [ 93 ].…”
Section: Conservation Strategies For Potato Plants---biocontrolmentioning
confidence: 99%